Age of joint venture, inter-firm technology transfer and local firms' performance - Abdul Wahab, Sazali; Abdullah, Haslinda; Uli, Jegak; Che Rose, Raduan (Canadian Center of Science and Education, 2010)
The inter-firm technology transfers (TT) through international joint ventures (IJVs), among others, have significantly contributed to a higher degree of local innovation performance/capabilities, technological capabilities, competitive advantage, organizational learning effectiveness, productivity, technological development of local industry, and the economic growth of the host country. Since the focus of inter-firm TT in developing countries has shifted to degree of technology transfer, organizations in developing countries are attempting to assess not only the significant role of technology transfer in strengthening their corporate and human resource performance but also the influence of other critical variables such as MNCs’ size, age of JVs (JVAGE), country of origin, and MNC’s type of industries that could significantly moderate the relationship. The main objective of this paper is to empirically examine the moderating effect of age of JV (old vs. young JVs) on the relationships between degree of inter-firm technology transfer and two dimensions of local firms’ performance: corporate and human resource performances. Using the moderated multiple regression (MMR) analysis, the theoretical models and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Companies of Malaysia (ROC). The results revealed that age of JV has significantly affected the relationships between degrees of technology transfer and both dimensions of local firms’ performance; where the relationships were found stronger for old JVs as compared to young JVs. The study has bridged the literature gaps in such that it offers empirical evidence and new insights on the significant moderating effects of age of JVs in the relationships between degree of inter-firm technology transfer and local firms’ performance using the Malaysian sample.